Bladder Wall Telangiectasia in a Patient with Ataxia-Telangiectasia and How to Manage? - Fatma Deniz Aygün; Serdar Nepesov; Haluk Çokuğraş; Yıldız Camcıoğlu (Hindawi Limited, 2015)
Ataxia-telangiectasia (A-T) is a rare neurodegenerative, inherited disease causing severe morbidity. Oculocutaneous telangiectasias are almost constant findings among the affected cases as telangiectasia is considered the main clinical finding for diagnosis. Vascular abnormalities in organs have been reported infrequently but bladder wall telangiectasias are extremely rare. We aimed to report recurrent hemorrhage from bladder wall telangiectasia in a 9-year-old boy with A-T who had received intravenous cyclophosphamide for non-Hodgkin's lymphoma. Since A-T patients are known to be more susceptible to chemical agents, we suggested that possibly cyclophosphamide was the drug which induced bladder wall injury in this patient.